Kesiapan Sekolah dalam Menghadapi Pembelajaran Deep Learning di SMA Negeri 1 Pulau Punjung - S, Rinny; Rahmawati, Aulia; Fatrisna, Yuli; Fazis, Muhammad (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to explore and analyze the readiness of SMA Negeri 1 Pulau Punjung in implementing Deep Learning learning, by emphasizing the perspective of organizational change management The method used is a qualitative case study, with the research subjects consisting of the principal, teachers, and staff involved in educational technology changes. The subjects were selected through purposive sampling by choosing informants considered most relevant and knowledgeable about the context of change within the school. Data collection techniques included interviews, observations, and document analysis. The results of the study indicate that school readiness is still in the early stages of transition, marked by collective awareness and initial efforts to train teachers, but is still constrained by infrastructure limitations, minimal teacher understanding of DL, and the absence of formal policies related to DL integration in the curriculum. The change process is analyzed using Kurt Lewin's change management theory, which shows that SMA Negeri 1 Pulau Punjung has only reached the unfreezing stage and part of the changing stage, while the refreezing stage is not yet optimal. Sustainable strategies are needed in the form of intensive training, strengthening school policies, improving infrastructure, and building a culture of innovation so that the transformation of deep learning learning can run effectively and sustainably